Implementasi Pengembangan Anak Usia Dini Holistik Integratif untuk Pencegahan Stunting - Afrianti, Nina; Yuliantina, Irma (Jurnal Tumbuh Kembang Anak Usia Dini, 2024)
The implementation of holistic early childhood development integration in PAUD units can also inhibit the increase in stunting rates that are so high, especially in villages that have programs to accelerate the reduction of stunting. In addition to optimizing early childhood nutrition, the village government also optimizes one village to have one PAUD teacher who is trained to increase his competence and quality of the program to accelerate the decline in stunting prevention and subscriptions. Parental education and knowledge is the main priority, which is a habit in the community when providing care and providing nutritional intake for early childhood growth and development in the home. The habit of parents in providing this parenting pattern is still a problem in using old patterns in parenting; this habit is something that often happens in each home. The village PAUD unit institution, TKIT Subulussalam, Banda Aceh City, is a research site that was researched using qualitative methods. Based on what was done in the field, the focus of research conducted by researchers turned out to be three factors that the community and parents did not know that the problem of stunting occurred in early childhood, namely: (1) unbalanced nutrition; (2) care that is not in accordance with the standards of child development achievement; and (3) personal hygiene and the environment where the child is or can be called clean and healthy living behavior